STUDENTS’ ENGLISH LEARNING STRATEGIES AT SENIOR HIGH SCHOOL IN LUBUKLINGGAU - Agus Triyogo; Hamdan Hamdan (JELLT (Journal of English Language and Language Teaching), 2018)
The present study aims to describe the students’ obstacles in learning English and their strategies in learning English at the senior high school. This study employs qualitative descriptive method. The data were collected through Focus Group Discussion (FGD) and interviews to get the naturality of the data. The study was conducted at SMA -Al -Ikhlas and SMA Negeri 8 Lubuklinggau, involving twenty students from both schools. The results indicate that many students of both schools have obstacles in learning English on pronunciation, understanding meaning and grammar.  Their learning strategies include social strategies, cognitive strategies, and meta-cognitive strategies.